The Phenomenon of Migrant Communities, Food Security and Their Participation - Purnomo, Didit (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
The study aimed to analyze and describe a strategy of food security achievement through land use at an area of migrant community. It was located in Wonogiri regency(an area with high migration), Central Java, Indonesia. It employed a mixed-method: quantitative and qualitative approach. The two approaches were used in the survey. The data collections used focus group discussions, in-depth interviews with key informants and participant observations. The results of the study formulated two strategies: land use strength and farmer institutional empowerment. The strategy of land use strength was divided into two scenarios. Scenario 1 referred to a maximal land use through essential food plant and agricultural extension (PPL). Scenario 2 referred to a non-maximal land use through diversification of food plant with a jajar legowo technique. The strategy of farmer institutional empowerment consisted of two scenarios. Scenario 1 referred to a high farmer institutional empowerment trough accompaniment. Scenario 2 referred to a low farmer institutional empowerment through accompaniment with standardization and development.